Tool mark analyses for the identification of palaeolithic art and modern graffiti. The case of Grottes d'Agneux in Rully (Saône-et-Loire, France). (September 2019) - Ruiz López, Juan F.; Hoyer, Christian T.; Rebentisch, Annika; Roesch, Anna Maria; Herkert, Klaus; Huber, Nadine; Floss, Harald
Abstract: The identification of technical traits derived from the analyses of photogrammetric 3D models can be used for archaeological objectives. In this paper, we are proposing a methodology for discrimination of parietal engravings based on 3D models build with photogrammetry software. Our case study are the caves of Agneux, two small caverns with an astonishing number of graffiti on their walls. Most of these graffiti were made since 19th century, but with some examples of depictions that are compatible with the technical features of Palaeolithic art. The analyses of the marks in some lines in Agneux I have demonstrated the use of different tools. Virtual illumination has been applied to identify and read words and dates which can be discarded as prehistoric. These results will be compared with replicative experiments. This methodology could be useful for the discrimination of prehistoric graphic expressions in panels with a biography of long-term human interventions. Graphical abstract: Image 1